Absorber layer optimisation of copper antimony sulfide thin film photovoltaics using numerical simulation. (October 2021) - Adewoyin, Adeyinka D.
Abstract: Recently, the ternary compound, CuSbS2, has been attracting a lot of interest in developing sustainable photovoltaic energy conversion because of its use as an absorber layer material due to the low toxicity, cost and abundance of constituents in nature. However, the recent conversion efficiencies reported for copper antimony sulfide (CAS) thin-film photovoltaics is still about 3%. Consequently, this research work is geared toward optimising the absorber layer material using numerical modelling and simulation to enhance the device performance. The simulation of the baseline model was achieved using the Solar Cell Capacitance Simulator (SCAPS-1D). Results of the simulation showed good agreement with experimental results. Subsequently, a step by step optimisation was done on the absorber layer. The optimisation process includes the variation of the acceptor concentration at various thicknesses, followed by the electron affinity and the back-contact metal work function. Results showed that the optimal carrier concentration of CuSbS2 is 1 × 10 17 c m − 3 at a thickness of 2.6 μm. The electron affinity of 4.15 eV was obtained as the optimum value of the absorber. Also, it suggests that the back contact electrode optimal work function is 5.0 eV, which corresponds to that of Molybdenum. A combination of these optimisations doubled the recent experimentally obtained photo-conversion efficiency with a value of 7.42%. Highlights: The model Al: ZnO/CdS/CAS/Mo structure has been simulated SCAPS-1D software and results showed good agreements with experimental values. The optimal carrier concentration of CuSbS2 was observed to be at 1 × 10 17 c m − 3 at a thickness of 2.6 μm. Further optimisation of the absorber's electron affinity of 4.15 eV and the back-contact metal work function of 5.0 eV enhanced the device performance. A combination of these optimizations doubled the experimentally obtained photo-conversion efficiency with a value of 7.42%.